Cost efficiency in Bangladesh banking: does financial reform matter? - Robin, I.; Salim, Ruhul; Bloch, Harry (Routledge, 2017)
This article estimates the cost efficiency of the commercial banks of Bangladesh in the context of financial reform. Employing the single-stage stochastic frontier analysis (SFA) model, the study uses a unique balanced panel data set comprising bank-level annual data from the dominant commercial banks in Bangladesh for the period 1983–2012. The results show that bank cost has fallen due to financial deregulation. Our results from the data envelopment analysis do not vary significantly that we obtained from the SFA. In addition, the presence of politically linked directors on the bank board has an adverse effect on efficiency. These findings suggest that further reforms aiming at removing all sorts of political influence should continue to ensure competitive environment in order to achieve cost efficiency in the financial sector of the country.